Staff conceptualisations of elder abuse in residential aged care: A rapid review. (30th July 2018) - Radermacher, Harriet; Toh, Ying Li; Western, Deborah; Coles, Jan; Goeman, Dianne; Lowthian, Judy
Abstract : Objective: The purpose of this rapid review was to explore how residential aged care staff conceptualise and identify elder abuse. Methods: English‐language publications, between 2000 and 2017, about elder abuse in residential aged care in developed countries were sought from three academic databases. Only perspectives on staff‐to‐resident and resident‐to‐resident abuse were included. Results: Over 2000 articles were screened, and 19 journal articles were included in the review. A wide range of abusive behaviours was identified, but there was little common understanding of what constituted elder abuse. Furthermore, disparities in conceptualisations were greater for certain types of abuse (e.g. verbal, psychological and caregiving). Conclusion: Elder abuse in residential aged care was conceptualised and identified by staff in diverse and different ways. This lack of common understanding hinders the development of effective interventions and prevention strategies, which include staff education and training as well as significant structural and institutional changes.